2022
DOI: 10.1016/j.celrep.2021.110268
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted neural correlates of anesthesia and sleep reveal early circuit dysfunctions in Alzheimer models

Abstract: Summary Dysregulated homeostasis of neural activity has been hypothesized to drive Alzheimer’s disease (AD) pathogenesis. AD begins with a decades-long presymptomatic phase, but whether homeostatic mechanisms already begin failing during this silent phase is unknown. We show that before the onset of memory decline and sleep disturbances, familial AD (fAD) model mice display no deficits in CA1 mean firing rate (MFR) during active wakefulness. However, homeostatic down-regulation of CA1 MFR is disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 123 publications
(184 reference statements)
1
14
0
1
Order By: Relevance
“…The binding of Aβ1-42 to CaMKII-positive synapses might explain why excitatory neurons, in particular, are affected. The increased frequencies and amplitudes of calcium oscillations that we observed with neprilysin inhibition as a means to elevate endogenous Aβ are consistent with results from Abramov et al (2009), showing increased release probability with thiorphan treatment in cultured hippocampal neurons. However, since neprilysin also degrades various enkephalins and peptide neurotransmitters, such as substance P, which can influence calcium stores (Heath et al, 1994), we additionally showed a lack of effect on calcium oscillations with neprilysin inhibition in APP KO neurons.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The binding of Aβ1-42 to CaMKII-positive synapses might explain why excitatory neurons, in particular, are affected. The increased frequencies and amplitudes of calcium oscillations that we observed with neprilysin inhibition as a means to elevate endogenous Aβ are consistent with results from Abramov et al (2009), showing increased release probability with thiorphan treatment in cultured hippocampal neurons. However, since neprilysin also degrades various enkephalins and peptide neurotransmitters, such as substance P, which can influence calcium stores (Heath et al, 1994), we additionally showed a lack of effect on calcium oscillations with neprilysin inhibition in APP KO neurons.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, we observed that the mean firing rates were similar between TTX, vehicle and bicuculline treated WT neurons after 48 h consistent with findings suggesting that while single unit firing is unstable, networks maintain surprisingly stable firing frequencies ( Slomowitz et al, 2015 ). Aβ and APP have been implicated in normal HSP ( Gilbert et al, 2016 ; Galanis et al, 2021 ), and APP/PS1 mice were recently shown to have defective downscaling during sleep ( Zarhin et al, 2022 ). Defective HSP could help explain why AD transgenic mice are more susceptible to pharmacologically-induced and spontaneous seizures ( Minkeviciene et al, 2009 ; Reyes-Marin and Nuñez, 2017 ) and could provide a framework for explaining the increased sensitivity to seizures in AD patients ( Pandis and Scarmeas, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data show that surgical-plane levels of PTB, ISO, and PRO all provide effective models to probe the mechanistic complexities of the coma-like brain state of burst suppression, such as cortical hyperexcitability [ 4 ], neurovascular coupling [ 37 ], and local cortical spatiotemporal dynamics [ 38 ]. Indeed, ISO was recently shown to exhibit the same dysregulation in homeostatic neural-firing rates as nREM in pre-symptomatic mouse models of familial Alzheimer’s disease [ 39 ], indicating that ISO may serve as a useful model to explore the connection between the subclinical epileptiform activity and network hyperexcitability that is observed in some models of Alzheimer’s disease [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the APP/PS1 mouse, Aβ has been shown to increase neuronal activity (Busche et al, 2008; 2012) as well as decrease neuron firing, perhaps explained by a neuron’s proximity to nearby plaques (Klee et al, 2020). This may also depend on brain state or context (Zarhin et al, 2022), highlighting the need to examine neuronal activity in multiple regions across a range of naturally occurring conditions. At a lower spatial resolution, APP overexpression reduces the power of gamma oscillations (Palop and Mucke, 2016) and alters coupling between the hippocampus and cortex during sleep (Zhurakovskaya et al, 2019).…”
Section: Discussionmentioning
confidence: 99%